Modulation of B Cells and Homing Marker on NK Cells Through Extracorporeal Photopheresis in Patients With Steroid-Refractory/Resistant Graft-Vs.-Host Disease Without Hampering Anti-viral/Anti-leukemic Effects - Wang, Lei; Ni, Ming; Hückelhoven-Krauss, Angela; Sellner, Leopold; Hoffmann, Jean-Marc; Neuber, Brigitte; Luft, Thomas; Hegenbart, Ute; Schönland, Stefan; Kleist, Christian; Sill, Martin; Chen, Bao-an; et al. (Frontiers in Immunology, 2018)
Graft-versus-host disease (GvHD), a severe complication of allogeneic hematopoietic stem cell transplantation, significantly affects the post-transplant morbidity and mortality. Systemic steroids remain the gold standard for the initial management of GvHD. However, up to 60% of patients will not sufficiently respond to steroids. Extracorporeal photopheresis (ECP), a cell-based immunotherapy, has shown good clinical results in such steroid-refractory/resistant GvHD patients. Given its immunomodulatory, but not global immunosuppressive and steroid-sparing capacity, ECP constitutes an attractive option. In the case of GvHD, the balance of immune cells is destroyed: effector cells are not any longer efficiently controlled by regulatory cells. ECP therapy may restore this balance. However, the precise mechanism and the impact of ECP on anti-viral/anti-leukemic function remain unclear. In this study, 839 ECP treatments were performed on patients with acute GvHD (aGvHD) and chronic GvHD (cGvHD). A comprehensive analysis of effector and regulatory cells in patients under ECP therapy included multi-parametric flow cytometry and tetramer staining, LuminexTM-based cytokine, interferon-γ enzyme-linked immunospot and chromium-51 release assays. Gene profiling of myeloid-derived suppressor cells (MDSCs) was performed by microarray analysis. Immunologically, modulations of effector and regulatory cells as well as proinflammatory cytokines were observed under ECP treatment: (1) GvHD-relevant cell subsets like CD62L+ NK cells and newly defined CD19hiCD20hi B cells were modulated, but (2) quantity and quality of anti-viral/anti-leukemic effector cells were preserved. (3) The development of MDSCs was promoted and switched from an inactivated subset (CD33-CD11b+) to an activated subset (CD33+CD11b+). (4) The frequency of Foxp3+CD4+ regulatory T cells (Tregs) and CD24+CD38hi regulatory B cells was considerably increased in aGvHD patients, and Foxp3+CD8+ Tregs in cGvHD patients. (5) Proinflammatory cytokines like IL-1β, IL-6, IL-8 and TNF-α were significantly reduced. In summary, ECP constitutes an effective immunomodulatory therapy for patients with steroid-refractory/resistant GvHD without impairment of anti-viral/leukemia effects.